Universal Health Coverage through Community Nursing Services: China vs. Hong Kong - Chan, Wai Yee (Rev Lat Am Enfermagem, 2017)
OBJECTIVE: this article looks at how the development of community nursing services in China and Hong Kong can enhance universal health coverage. METHODS: literature and data review have been utilized in this study. RESULTS: nursing services have evolved much since the beginning of the nursing profession. The development of community nursing services has expanded the scope of nursing services to those in need of, not just hospital-level nursing care, but more holistic care to improve health and quality of life. CONCLUSION: despite the one-country-two-systems governance and the difference in population and geography, Hong Kong and China both face the aging population and its complications. Community nursing services help to pave the road to Universal Health Coverage.